Awareness and Prevalence of Needle Stick Injury among Nursing Students at King Abdulaziz University - Ohoud K. Almuslami; Sarah S. Fadul; Shahad S. Munshi; Fatmah M. Sangoof; Naded A. Mersal (Evidence-Based Nursing Research)
Context: Nurses and other health care workers, and at the same time nursing students in clinical training, are at high risk for needle stick injury. The main problem is that needle stick injury (NSIs) can lead to an increase in the risk of over 20 types of infection transmission among health care workers (HCWs), and the most dangerous infections are hepatitis C virus (HCV), hepatitis B virus (HBV), and human immunodeficiency virus (HIV).